The association of sun-cured tobacco and cigarette use with global cognitive function, verbal fluency and memory in patients with chronic obstructive pulmonary disease: A cross-sectional study - Xiaomei Chen; Jie Li; Jia Liu; Xiao Liu; Menghui Deng; Xunhu Dong; Yanni Yang (Tobacco Induced Diseases)
Introduction Some elderly people in China prefer sun-cured tobacco to cigarettes, and the composition of sun-cured tobacco and cigarettes is inconsistent. The influence of cigarettes on the cognitive function of COPD patients has been widely reported, but the research on sun-cured tobacco is relatively rare. Our study explored the association of sun-cured tobacco and cigarette use with cognitive decline in COPD patients.